Testing English Language Skills of Under-graduate Technical Students in Campus Placements - Dr. M. Madhu Sudhan Rao, Dr. Mohammad Rezaul Karim (International Journal of Advanced Science and Technology, 2020)
All India Council of Technical Education(AICTE), India, permitted thousands of societies or academies or trusts to set up engineering colleges wherever they liked in 2008. There was a drastic change in campus placement testing procedures due to many engineering colleges in India since then. After 2010, most of the companies in India focussed on conducting campus placements in engineering colleges uniquely. Companies started testing the English language competency of engineering students at various levels in campus placements. Initially, the basic knowledge of grammar was tested by most of the companies while recruiting students through campus placements. Slowly, the level of testing students’ English proficiency got raised. A few software companies like ADP, Accenture, etc., focussed on testing the language skills of the students at the Graduate Record Exam (GRE) level in 2012. There was a paradigm shift in 2014 by TCS in testing students’ language skills. For the first time pan India, students’ writing ability was tested through online, on-campus placements by TCS. Interestingly, the evaluation was done by machine instead of a man like in the Test of English as a Foreign Language (TOEFL) writing module.